Post operative pain comparison of nasal pack with trans-septal suturing after septoplasty - Muhammad Awais; Khansa Tariq; Muhammad Umar Farooq; Uzma Sagheer; Mahrukh; Humayun Suqrat Hasan Imam (Journal of University Medical & Dental College, 2025)
BACKGROUND AND OBJECTIVE: Septoplasty, first introduced in the late modern period, has undergone several refinements and remains one of the most frequently performed nasal surgeries, alongside inferior turbinoplasty, endoscopic sinus surgery, and rhinoplasty. Postoperative pain management remains a significant consideration, particularly regarding the use of nasal packing versus transeptal suturing. This study aimed to compare pain perception between patients who received nasal packing and those who underwent transeptal suturing after septoplasty. METHODOLOGY: A quasi-experimental study was conducted in the Department of ENT at Aziz Fatimah Hospital, following approval by the Ethical Research Committee, from October 2023 to March 2024. A total of 84 patients were enrolled and divided equally into two groups. Group A received polyvinyl alcohol nasal packing, while Group B underwent trans-septal suturing using Vicryl® 3-0 absorbable sutures. Postoperative pain was assessed using the Visual Analogue Scale (VAS) after 48 hours during hospital stay and again on day 7 during follow-up. RESULTS: Of the 84 participants, 29 (34.5%) were female and 55 (65.5%) were male, with ages ranging from 18 to 54 years (mean 24.20 ± 6.937). No statistically significant difference in postoperative pain was observed between the two groups, with p-values of 0.0836 at 48 hours and 0.356 at day 7. CONCLUSION: The study concludes that nasal packing and transeptal suturing are comparable in terms of postoperative pain after septoplasty, with no significant difference between the two methods.